REALIZATION PRINCIPLE OF POLITENESS IN INTERNET DISCUSSION AMONG THREE HINDUS OF INDONESIAN DISCUSSION GROUP - Wayan Pageyasa (Journal of English Education, 2016)
This study aims to gain a deep understanding of the realization of the principle of politeness in internet discussion in three Indonesian Hindu discussion group. Realization of politeness principle consists of compliance and violations. The research paradigm was qualitative. The method used was the pragmatic content analysis and inductive procedures. The research data was in the form of quotations dialogue in internet discussion that contains the realization of the principles of politeness. The data was obtained from the written record dialog in Internet discussion in three Hindu Indonesia group discussions. The results showed that in general the principle of politeness tends to be obeyed. It means that those involved in internet discussion in three Indonesian Hindu discussion group were generally considered polite in speaking.